2010
DOI: 10.1007/s10592-010-0125-5
|View full text |Cite
|
Sign up to set email alerts
|

Threatened populations of the Australian squirrel glider (Petaurus norfolcensis) show evidence of evolutionary distinctiveness on a Late Pleistocene timescale

Abstract: The squirrel glider Petaurus norfolcensis occurs across a broad Australian latitudinal range that includes gaps in distribution and potential biogeographic barriers, creating the potential for evolution of distinct entities within this species. Because of the species' threatened status in the southern part of its range, we tested for the presence of geographically based independent evolutionary units among gliders sampled from southern, and northern coastal populations, using sequences of mitochondrial cytochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 58 publications
3
24
2
Order By: Relevance
“…, 2008). Divergence between these major regions is generally dated to the Late Miocene–Pliocene, suggesting reinforcement of genetic patterns over multiple climatic cycles, although phylogeographical structure in squirrel gliders between eastern coastal and south‐eastern inland regions reflects Late Pleistocene influences (Pavlova et al. , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…, 2008). Divergence between these major regions is generally dated to the Late Miocene–Pliocene, suggesting reinforcement of genetic patterns over multiple climatic cycles, although phylogeographical structure in squirrel gliders between eastern coastal and south‐eastern inland regions reflects Late Pleistocene influences (Pavlova et al. , 2010).…”
Section: Resultsmentioning
confidence: 99%
“…P. norfolcensis, although rare in the studied assemblages, was identified from all three examined deposits and persists today in the upper south east region (Van dyck & Strahan 2008; department for environment and heritage and South east natural Resources management board, no date). While the absence of P. norfolcensis from middle to late Pleistocene aged assemblages may be a false absence such that the species is present but has not yet been detected, it is also possible that range expansion through population dispersal did occur into the naracoorte region at a similar time as northward expansion from Victorian and new South Wales populations in the late Pleistocene, as reflected in the species' phylogeography (Pavlova et al 2010). Genetic analysis of P. norfolcensis across its distribution from south eastern South Australia, along the east coast of Australia to the Wet tropics bioregion in Queensland, showed that populations south and inland of the Great dividing Range have been undergoing decline since the northward expansion of the species in the middle to late Pleistocene, prior to the lGm (Pavlova et al 2010).…”
Section: Faunal Turnover and Biogeographic Implicationsmentioning
confidence: 99%
“…While the absence of P. norfolcensis from middle to late Pleistocene aged assemblages may be a false absence such that the species is present but has not yet been detected, it is also possible that range expansion through population dispersal did occur into the naracoorte region at a similar time as northward expansion from Victorian and new South Wales populations in the late Pleistocene, as reflected in the species' phylogeography (Pavlova et al 2010). Genetic analysis of P. norfolcensis across its distribution from south eastern South Australia, along the east coast of Australia to the Wet tropics bioregion in Queensland, showed that populations south and inland of the Great dividing Range have been undergoing decline since the northward expansion of the species in the middle to late Pleistocene, prior to the lGm (Pavlova et al 2010). Unfortunately, there were only two samples from South Australia used in the genetic analyses which makes it unclear the extent to which patterns of historical population dynamics and occupancy apply in this region; however, it appears unusual that the species is apparently absent from >70 ka aged deposits of the nCWhA when divergence of the most recent common ancestor of the species has been dated from the early to middle Pleistocene (Pavlova et al 2010).…”
Section: Faunal Turnover and Biogeographic Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These populations are considered to be under a greater threat of extinction than northern, coastal populations, due to a lower effective (and declining) population size (Pavlova et al . ). The legislative status of the Squirrel Glider nationally does not distinguish between the two genetic groups, and the species has no federal listing.…”
Section: Introductionmentioning
confidence: 97%